Notes on Anqasha picta (Pocock, 1903) and description of a new species of Anqasha from Peru (Araneae, Theraphosidae, Theraphosinae) - Kaderka, Radan (2023)
The monotypic Peruvian genus Anqasha with type species Anqasha picta (Pocock 1903) is revised. A female of A. picta from the type locality of Caraz is herein described for the first time. The recently described females of A. picta coming from Recuay are transferred to the new taxon, which is herein described, diagnosed, and illustrated. Males of A. minaperinensis sp. nov. differ from that of A. picta in the shape of retrolateral branch of subapical apophyses on male tibia I, which is apically flattened and having three short spines. Females of A. minaperinensis sp. nov. differ from A. picta in the shape of seminal receptacles. LSIDurn:lsid:zoobank.org:pub:5ACC070E-ED16-4FBE-B6B5-F8EFC0FED2C7Acto nomenclatural/nomenclatural act:Anqasha minaperinensis Kaderka, 2023LSIDurn:lsid:zoobank.org:act:99084678-F808-434C-80AE-A101C4338C85